2009
DOI: 10.1021/jp808645e
|View full text |Cite
|
Sign up to set email alerts
|

Initial Study on the Toxicity of Silver Nanoparticles (NPs) against Paramecium caudatum

Abstract: In this initial study, the toxicity effect of silver NPs against a model unicellular eukaryotic organism of Paramecium caudatum was studied. For the purpose of this study, a dialysis-based method was adapted, which allowed the preparation of stable aqueous dispersions of silver NPs in various silver concentrations that were necessary for the evaluation of toxicity limits of these particles. The obtained results demonstrate that the silver NPs do not exhibit any toxicity action against the tested unicellular eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 19 publications
5
72
2
4
Order By: Relevance
“…56,57 Antifungal activity of nano-Ag [29][30][31]56 has been also suggested in the present investigation. The results suggest that nano-Ag may exert a fungicidal activity by destroying cell membrane integrity ( Figure 6).…”
Section: Dovepresssupporting
confidence: 65%
See 2 more Smart Citations
“…56,57 Antifungal activity of nano-Ag [29][30][31]56 has been also suggested in the present investigation. The results suggest that nano-Ag may exert a fungicidal activity by destroying cell membrane integrity ( Figure 6).…”
Section: Dovepresssupporting
confidence: 65%
“…The results suggest that nano-Ag may exert a fungicidal activity by destroying cell membrane integrity ( Figure 6). Other results 30 have also shown that fungal cells treated with nano-Ag show significant damage, characterized by the formation of a pit in their cell walls and pores in their plasma membrane.…”
Section: Dovepressmentioning
confidence: 76%
See 1 more Smart Citation
“…In aquatic invertebrates, some data show that Ag + has an enhanced toxicity if present as nanoparticles due to the result of following release from the NP as ionic Ag (Griffitt et al, 2008;Roh et al, 2009). On the other hand, it has been demonstrated that AgNPs can be less toxic than Ag + (Kvitek et al, 2009;Griffitt et al, 2009). The toxicity of AgNPs to the freshwater alga, C. reinhardtii, appeared to be much greater than silver ions when comparing an equal mass of Ag + , indicating a potential NP-mediated effect due to the interaction of the NP with the algal cells (Navarro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…colloidal stability. [17][18][19][20][21][22] Despite the simple method of preparation of AgNPs and mild reaction conditions of this process, an in-depth understanding of the mechanistic factors that control AgNP formation using Tollens' reagent is lacking.…”
Section: Introductionmentioning
confidence: 99%